Quem merece ser cuidado? a experiência do cuidado junto aos jovens autores de ato infracional - Manzini, Juliane Macedo (2020)
In the scenario of public policies aimed at adolescence, we have perceived the stalemates in the field of practices and knowledge, being particularly problematic when we face contexts of intense vulnerability in which the young people who live in poverty and marginality are also involved with the criminal justice system. We know that such difficulties come from a long time, especially in the case of young offenders, as well as the challenges in the care provided among the different services intended for them. Given this context, starting from the interface between health and justice, this study investigates the care given at this moment to the field of youth mental health. To this end, it analyzes the care practices in a Children and Young Psychosocial Care Center (CAPSi) and the effects of this logic in relation to young offenders. As a research method, we started from the cartographic perspective that allowed us to follow the procedural dimension of the reality in which young people are inserted, as well as to investigate certain psychosocial landscapes that make up the daily care. The research was developed at CAPSi located in a medium-sized municipality in the state of São Paulo, from the confluence among the following methodological procedures: survey of medical records in order to investigate the institutional path of adolescents attending the service; identification of data contained in the medical record book; interviews with employees who work in the mental health area and with a young person and his legal guardian, as well as the participation in the activities developed in CAPSi operating dynamics. From the follow-up of the adolescents’ path, and through the workers' practices, it is clear that CAPSi has played a central role in the care of young offenders, mainly due to the difficulty in intersectoral articulation, which interferes in the care offered, leading to fragility in the adhesion to the treatment. Although there is contact with other services, we generally realize that the organized care towards young offenders is limited to two specific sectors: mental health and justice, eliminating any agreements that should be made by other necessary instances with the population attended. Moreover, it is noted that the so-called therapeutic resources are restricted to a logic of care based on procedures and protocols, whose service is given at CAPSi. We perceived that there is some willingness by the professionals to rethink their own activities, as well as a recognition by some family members to think CAPSi as a possible care alternative in which to seek support for their own needs and the needs of the children attended. However, the conditions in which CAPSi is inserted - work overload, bureaucratized practices crossed with good intentions - tend to lead the team to a limited action, which may compromise CAPSi's viability to become creative and powerful, capable of generating visible and relevant transformations in people’s lives. In our research experience, it was also possible to expand the notion of care, without restricting it to the health field, as a necessary attribute of human survival. In this conception, therefore, care refers to an expression of intense social support, together with solidarity and willingness to be together, in which reception, listening, bonding and trust are fundamental elements in this experience